Sit to Stand Muscle Power Reference Values and Their Association with Adverse Events in Colombian Older Adults - Garcia-Hermoso, A (Nature Research, 2022)
Recently, a valid method to assess lower-body muscle power based on a sit-to-stand field test (STS) has been published. Our study aimed to describe lower-body muscle power in older individuals aged ≥ 60 years and examine the relationship of muscle weakness with adverse events according to gender- and age-specific muscle weakness cut-off points. A total of 3689 Colombian older adults (57.6% women, age 69.1 ± 6.9 years) from the 2015 Survey on Health, Well-Being, and Aging in Latin America and the Caribbean (SABE) participated in this study. Lower-body muscle power normalized to body mass was estimated by the five-repetitions STS test. Anthropometric, physical performance and clinical characteristics were collected. Age-specific percentiles using the LMS method, cut-off points and association with adverse events were calculated. Lower-body muscle power was greater in men than among women (2.2 ± 0.7 vs. 1.6 ± 0.5 W·kg−1, respectively; p < 0.001) at all ages. Muscle power ranked in the 50th percentile between 2.38 and 1.30 W·kg−1 in men, whereas women ranked between 1.79 and 1.21 W·kg−1. According to the cut-off points, lower-limb muscle power < 1 standard deviation in men was associated with having dynapenia, poor gait speed, cognitive impairment and mental, visual, hearing and memory problems. While, women were associated with having sarcopenia, dynapenia, poor gait speed, cognitive impairment, mental, hearing and memory problems, dementia and hospitalizations of > 24 h in the last year. Overall, participants with poor lower-limb muscle power had a significantly higher risk of adverse events [in men: odds ratio (OR) = 1.51, 95% confidence interval (CI) = 1.19–1.91, p < 0.001; in women: OR = 1.52, 95% CI = 1.27–1.87, p = 0.001] than their stronger counterparts. This study is the first to describe lower-limb muscle power values and cut-off points among a nationally representative sample of Colombian older adults. In men, 7 of the 14 adverse events studied were associated with lower muscle strength, whereas in women, it was 9 of the 14 adverse events. © 2022, The Author(s).